The Use of Cluster Analysis in Assessing the Sustainability of Organic Farms. Part I. Methodical Considerations (Agricultural Engineering, 2019)
The modern agriculture model is a model based on the principles of sustainable development, i.e. protecting the environment and the cultural landscape on the one hand, and on the other, ensuring adequate income for residents. It is based on three orders: ecological, social and economic. This paper attempts to use cluster analysis to assess the economic and ecological sustainability of organic farms. It also indicates the factors that statistically influenced the assessment of a farm as sustainable, or not. The first part of the work is dedicated to the characteristics of the problem and the methodology of research and analysis. The second part contains the results of the research and discusses them.